Tideglusib Rescues Neurite Pathology of SPG11 iPSC Derived Cortical Neurons - Pozner, Tatyana; Schray, Annika; Regensburger, Martin; Lie, Dieter Chichung; Schlötzer-Schrehardt, Ursula; Winkler, Jürgen; Turan, Soeren; Winner, Beate (Frontiers in Neuroscience, 2018)
Mutations in SPG11 cause a complicated autosomal recessive form of hereditary spastic paraplegia (HSP). Mechanistically, there are indications for the dysregulation of the GSK3β/βCat signaling pathway in SPG11. In this study, we tested the therapeutic potential of the GSK3β inhibitor, tideglusib, to rescue neurodegeneration associated characteristics in an induced pluripotent stem cells (iPSCs) derived neuronal model from SPG11 patients and matched healthy controls as well as a CRISPR-Cas9 mediated SPG11 knock-out line and respective control. SPG11-iPSC derived cortical neurons, as well as the genome edited neurons exhibited shorter and less complex neurons than controls. Administration of tideglusib to these lines led to the rescue of neuritic impairments. Moreover, the treatment restored increased cell death and ameliorated the membranous inclusions in iPSC derived SPG11 neurons. Our results provide a first evidence for the rescue of neurite pathology in SPG11-HSP by tideglusib. The current lack of disease-modifying treatments for SPG11 and related types of complicated HSP renders tideglusib a candidate compound for future clinical application.